Förster Resonance Energy Transfer Sensitized Singlet Fission in BODIPY-Pentacene Dimer Conjugates - Wollny, Anna-Sophie; Lavarda, Giulia; Papadopoulos, Ilias; López-Duarte, Ismael; Gotfredsen, Henrik; Hou, Yuxuan; Tykwinski, Rik R.; Torres, Tomás; Guldi, Dirk Michael (Advanced Optical Materials, 2023)
In the present work, the energy donor 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) is used for the first time in combination with a pentacene dimer (Pnc2) to provide the conjugate BODIPYPnc2 that features absorption throughout a large part of the solar spectrum. Upon photoexcitation, the singlet excited state energy of BODIPY is transferred to the pentacene dimer via intramolecular Förster resonance energy transfer (FRET). Subsequently, the pentacene dimer undergoes intramolecular singlet fission. In this process, a singlet correlated triplet pair is generated from the first singlet excited state via coupling to an intermediate state. The results show that solvent polarity has an influence on the system, with the largest FRET rate (i.e., 7.46 × 1011 s−1) being obtained in the most polar solvent (namely, benzonitrile) along with the largest triplet quantum yield (i.e., 207 ± 20%).
CRIS-Team Scopus Importer:2023-10-13
Keywords: BODIPY; down conversion; energy transfer; pentacene; photoenergy conversion; singlet fission; time-resolved spectroscopy